2021
DOI: 10.1103/physreva.104.063715
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-wave generation of photon pairs in silica nanofibers using single-longitudinal- and multilongitudinal-mode pumps

Abstract: In this paper, we describe experimental observation and characterization of emission of photons pairs through FWM in a silica nanofiber, with high Coincidence to Accidental Ratio (at best greater than 20000 in the CW regime at pump power 24mW and 40000 in the pulsed regime at pump around 150µW) and high pair emission rate (above 1MHz in the pulsed regime with CAR around 100 at a pump power around 7mW), despite residual presence of Raman spontaneous scattering (in the vicinity of the 12 th silica Raman band) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Likewise, in 2019 Kim et al realized the generation of photon pairs via a spontaneous FWM process using a 12-cm-long 615-nm-diameter MNF [281] . In 2021, Delaye et al reported the emission of photon pairs by the FWM in a silica MNF, with a high coincidence to accidental ratio and high pair emission rate [212] . On the other hand, Abdul Khudus et al demonstrated parametric amplification through the FWM in silica MNFs with a wavelength band over 1000 nm in 2016 [282] .…”
Section: Four-wave Mixingmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, in 2019 Kim et al realized the generation of photon pairs via a spontaneous FWM process using a 12-cm-long 615-nm-diameter MNF [281] . In 2021, Delaye et al reported the emission of photon pairs by the FWM in a silica MNF, with a high coincidence to accidental ratio and high pair emission rate [212] . On the other hand, Abdul Khudus et al demonstrated parametric amplification through the FWM in silica MNFs with a wavelength band over 1000 nm in 2016 [282] .…”
Section: Four-wave Mixingmentioning
confidence: 99%
“…Therefore, we can finely tailor the total dispersion (combined material and waveguide dispersions) to be zero, positive, or considerably negative by controlling the MNF diameter and length. In practice, effective dispersion management using subwavelength-diameter MNFs has been widely applied for supercontinuum generation [78,80] , FWM [75] , ultrafast fiber lasers [82,83,209,210] , and quantum optics [211,212] .…”
Section: Optical Waveguiding Properties Of the Mnfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photon-pair generation using photonic crystal fibers (PCF) 17 , dispersion-shifted fibers 18 , 19 , step-index multimode optical fibers (MMF) 20 , graded-index MMF 21 , and birefringent fibers 22 has been reported as well. Among these optical fiber alternatives, PCFs and microstructured fibers exhibit unique characteristics that make them an attractive medium for photon-pair source implementations 9 , 23 26 . They exhibit engineered dispersion properties enabling spectrally or temporally tailored two-photon state generation, and high effective nonlinear coefficients permitting large emission rates.…”
Section: Introductionmentioning
confidence: 99%